NFM-03. EFFECT OF NEUROFIBROMATOSIS TYPE 1 ON LONG-TERM HEALTH OUTCOMES IN ADULT SURVIVORS OF CHILDHOOD ASTROCYTOMA: A REPORT FROM THE CHILDHOOD CANCER SURVIVOR STUDY. Issue 2 (22nd June 2018) - de Blank, Peter; Li, Nan; Ullrich, Nicole; Fisher, Michael J; Bhatia, Smita; Yasui, Yutaka; Sklar, Charles; Leisenring, Wendy; Howell, Rebecca; Oeffinger, Kevin; Hardy, Kristina; Fatih Okcu, M; et al.
Abstract: PURPOSE: The effect of neurofibromatosis type 1 (NF1) on incidence and severity of health outcomes in adult survivors of childhood astrocytoma is poorly understood. METHODS: 1, 617 >5yr survivors of childhood astrocytoma (147 NF1 survivors and 1, 470 non-NF1 survivors matched on diagnosis and diagnosis decade) and 5, 051 siblings were compared on self-reported chronic medical conditions (CTCAE v4.0) and cognitive impairment (defined as >90 th percentile of siblings on the CCSS Neurocognitive Questionnaire) using logistic and Poisson regression adjusted for age at survey, age at diagnosis, sex, race, CNS radiation and other treatment exposures. RESULTS: Among astrocytoma survivors, NF1 survivors (mean age 6.6yr at diagnosis) received chemotherapy (24% vs 13%) and carboplatin (71% vs 40%) more frequently than non-NF1 survivors. Compared to non-NF1 survivors, NF1 survivors were more likely to report a serious health condition (grade 3-4, RR[95%CI] 1.9[1.5-2.4]) and multiple chronic medical conditions (grade 2-4, 1.7[1.4-2.1]). Specifically, NF1 survivors were at increased risk for vision loss (1.8[1.5-2.1]), gastrointestinal disease (1.8[1.5-2.1]), heart disease (1.5[1.2-2.0]), lung disease (1.4[1.2-1.6]), and motor (1.2[1.1-1.4]) and sensory (1.2[1.0-1.4]) impairments. Interestingly, compared to both non-NF1 survivors and siblings, diabetes (0.2[0.1-0.3] vs non-NF1; 0.3[0.2-0.5] vs siblings) and abnormal thyroid (0.2[0.2-0.3] vs non-NF1; 0.6[0.5-0.8] vs siblings) were less common in NF1 survivors. NF1 survivors reported more impairment on emotional regulation (OR 2.0[1.1-3.7]), task completion (2.0[1.2-3.5]) and learning/memory (1.5[1.3-1.8]), and attended college less frequently (0.5[0.2-0.9]) compared to non-NF1 survivors. CONCLUSION: NF1 impacts risk of health/cognitive outcomes in adult survivors of childhood astrocytoma. Further research should investigate the underlying mechanisms of these risks.